THE INFLUENCE OF MARKETING MIX ON SATISFACTION AND LOYALTY OF RICE CUSTOMERS AT PT. KOMODITI TANI INDONESIA - Zulfarida Solihiyah, Erni Dwi; Widayanti, Sri; Syah, Mirza Andrian (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
Customers are the most crucial aspect of running a business, so companies need to maintain customer satisfaction. Customers who are satisfied with a product will generally have a loyal attitude towards that product. This research aims to analyze the influence of the marketing mix on customer satisfaction, customer loyalty, and rice customer loyalty at PT. Komoditi Tani Indonesia. The sampling method uses accidental sampling with a total of 68 respondents. The analysis used is SEM-PLS with the WarpPLS 8.0 program. The research results show that product, price, location, and employee variables have a significant effect on customer satisfaction. Product variables, price, location, physical facilities, and customer satisfaction significantly affect customer loyalty. The customer satisfaction variable mediates the relationship between product, price, and location variables on customer loyalty